The association between psychosocial factors and musculoskeletal symptoms among construction workers - Morli, Girthan; Mohd Khairul Izamil, Zolkefley (2022)
Construction workers are usually required to do labour-intensive and physically demanding activities (including psychosocial), affecting the health and well-being of employees. This study aims to identify the association of psychosocial factors with musculoskeletal symptoms among construction workers. A total of 72 construction workers were involved in this study. The musculoskeletal discomfort and psychosocial factors data were collected from a composite questionnaire including the Nordic Musculoskeletal Questionnaire (NMQ) and the Malaysian version of Copenhagen Psychosocial Questionnaire (BM-COPSOQ) respectively. Descriptive analysis of test data was performed to determine the prevalence of psychosocial factors and musculoskeletal symptoms among construction workers. The Chi-Square test was used in determining the association between psychosocial factors and the development of musculoskeletal disease (MSD). All p - values were set at 2-tailed. The significant values p ≤ 0.05 were considered statistically significant. The shoulder had the highest frequency of musculoskeletal discomfort (82%), followed by lower back (73.6%), knees (72.2%), upper back (70.8%), feet and elbow (66.7%), hip/thighs and forearm (62.5%), and neck (61.1%). It was shown that most psychosocial factors were found to have a statistically significant relationship with musculoskeletal symptoms at any of the body regions (p<0.05). There was significant relationship between certain psychosocial factors and musculoskeletal symptoms among construction workers. Identification of these factors and a proper workplace organizational management and culture should be implemented to reduce the risk of musculoskeletal pain.